Tossing Yee Sang: a unique way of celebrating Chinese New Year in Malaysia / Ong Sheau Fen - Ong, Sheau Fen (Academy of Language Studies, 2024)
The Chinese New Year is celebrated worldwide, with different regions having their unique ways of celebrating. In Malaysia, one distinctive tradition is the prosperity toss, known as Yee Sang. It's believed that Yee Sang was created by Loke Ching Fatt, who aimed to promote his catering business. When he started serving this dish, it gained incredible popularity, attracting people from various places. As a result, other businesses and the community began serving Yee Sang too. This tradition led to the gradual spread of the custom of eating Yee Sang within the Chinese society in Malaysia. Over time, Yee Sang has become an essential dish served during the Chinese New Year. Yee Sang is a special salad featuring raw fish, cucumber, carrot strips, pickled ginger, peanuts, vegetable oil, five spice powder, and plum sauce. It symbolizes prosperity and long life. Before eating it, people mix Yee Sang by tossing it up, known as "lo hei" in Cantonese. "Lo" signifies tossing for good fortune, while "hei" means to rise. This act of tossing Yee Sang signifies seeking good luck and wealth. People also express their hopes for the new year by offering good wishes while tossing it, aiming for their wishes to come true. Tossing Yee Sang not only enhances the festive atmosphere but also fills those eating it with the spirit of the new year. To our Muslim friends in the department, I suggest trying Sushi King's Yee Sang. It's delicious and reasonably priced. Why not bring your family to Sushi King this Chinese New Year and enjoy something new?